Integrable e-lements for statistics education - Wolfgang Karl Härdle; Sigbert Klinke; Uwe Ziegenhagen (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
Without doubt modern education in statistics must involve practical, computer-based data analysis but the question arises whether and how computational elements should be integrated into the canon of methodological education. Should the student see and study high-level programming code right at the beginning of his or her studies? Which technology can be presented during class and which computational elements can re-occur (at increasing level of complexity) during the different courses? In this paper we address these questions and discuss where e-techniques have their limits in statistics education.
Keywords: I21; C19; 330; electronic books; hypertext; e-supported teaching; statistical software